2019
DOI: 10.1002/jcb.28772
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Smad4 gene silencing enhances the chemosensitivity of human lymphoma cells to adriamycin via inhibition of the activation of transforming growth factor β signaling pathway

Abstract: There are diverse investigations focused on the therapies of lymphoma. Our research was taken to identify the effects of lentiviral‐mediated Smad4 gene silencing on chemosensitivity of human lymphoma cells to adriamycin (ADM) via transforming growth factor β (TGFβ) signaling pathway. Raji/ADM cells were cultured and infected with lentiviral particles Smad4‐short hairpin (shRNA) and control‐shRNA. Then, the messenger RNA (mRNA) and protein levels of TGFβ signaling pathway–related factors (Smad4, Smad3, cyclinE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Upregulation of CXC chemokine ligand 9 promotes viability and migration that can be abolished by knocking down of β-catenin in DLBCL cells [28], suggesting that Wnt/β-catenin signaling pathway plays an important role in DLBCL cell migration. Moreover, in Raji/ADM cells (B-cell non-Hodgkin’s lymphomas), inhibiting the activation of TGFβ signaling pathway via silencing Smad4 contributes to the suppression of cell viability, invasion and migration [29]. In addition, previous studies have shown that USP14 is an important regulator in Wnt/β-catenin signaling pathway by deubiquitinating Dvl [30].…”
Section: Resultsmentioning
confidence: 99%
“…Upregulation of CXC chemokine ligand 9 promotes viability and migration that can be abolished by knocking down of β-catenin in DLBCL cells [28], suggesting that Wnt/β-catenin signaling pathway plays an important role in DLBCL cell migration. Moreover, in Raji/ADM cells (B-cell non-Hodgkin’s lymphomas), inhibiting the activation of TGFβ signaling pathway via silencing Smad4 contributes to the suppression of cell viability, invasion and migration [29]. In addition, previous studies have shown that USP14 is an important regulator in Wnt/β-catenin signaling pathway by deubiquitinating Dvl [30].…”
Section: Resultsmentioning
confidence: 99%
“…The SMAD2/3/4 complex is translocated to the nucleus, where it binds to DNA and regulates the transcription of several genes (31,32). Increased mRNA and protein expression levels of SMAD3 and SMAD4 promote cell proliferation, migration and invasion (33). Previous studies have shown that the TGF-β/SMAD signaling pathway can regulate the proliferation of choriocarcinoma cells (15,16).…”
Section: Discussionmentioning
confidence: 99%